2021
DOI: 10.1108/ara-09-2020-0142
|View full text |Cite
|
Sign up to set email alerts
|

Does disclosure of earnings forecasts regulation affect the valuation of IPOs? Evidence from an emerging country

Abstract: PurposeThis paper aimed to explore the effect of a regulatory change pertaining to earnings forecasts disclosure from a mandatory to a voluntary regime on the valuation of Malaysian initial public offerings (IPOs).Design/methodology/approachThe study employed ordinary least square (OLS) regression and quantile regression to analyse the impact of disclosure of earnings forecasts regulation on the valuation of IPOs which comprised 458 IPOs reported for the period 2000–2017 on Bursa Malaysia.FindingsThis paper re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 64 publications
0
2
0
Order By: Relevance
“…A stock is considered as under-priced when the offer price is lower than the closing price on the first day of listing. The dummy variable of pricing mechanism takes a value of 1 if the IPO was priced using the book-building mechanism, and 0 if it was priced using the fixed price mechanism (Pu and Wang, 2015; Ong et al , 2021).…”
Section: Methodsmentioning
confidence: 99%
“…A stock is considered as under-priced when the offer price is lower than the closing price on the first day of listing. The dummy variable of pricing mechanism takes a value of 1 if the IPO was priced using the book-building mechanism, and 0 if it was priced using the fixed price mechanism (Pu and Wang, 2015; Ong et al , 2021).…”
Section: Methodsmentioning
confidence: 99%
“…Ammer and Ahmad-Zaluki (2017) posit that voluntary earnings forecast disclosures can be effective in improving the accuracy of earnings forecasts. However, a recent study by Ong et al (2021) found that under a voluntary regime, Malaysian IPOs that disclosed earnings forecasts were undervalued by underwriters due to investors' belief that the information on earnings forecasts in IPO prospectuses was inaccurate. It is difficult for earnings forecasts to be accurate due to unanticipated variables.…”
Section: Introductionmentioning
confidence: 99%